PENGARUH HARGA DAN FREE WI-FI TERHADAP KEPUTUSAN PEMBELIAN PRODUK PADA ANGKRINGAN DI KECAMATAN KARAS KABUPATEN MAGETAN - Rizal Ula Ananata Fauzi (Jurnal Aplikasi Bisnis, 2018)
This study aims to analyze the influences of price and Free Wi-Fi on consumer purchasing decisions at angkringan In Karas Magetan district The specific objective of this esearch is to know how the influence of Price Variables on Consumer Purchasing Decisions On Angkringan in Karas Magetan district. To provide know the influence of Variable Free Wi-Fi to Decision Purchase consumer On Angkringan in District Karas Magetan District. The research method used in this research with quantitative approach. Population in this research is all consumer of Angkringan in district of Karas Magetan Regency. samples taken are consumers angkringan for 3 months in Karas district, Magetan regency. Based on the formula Rao Purba, the number of samples taken as many as 97 respondents. Data collection techniques were conducted by using questionnaires and interviews, while data processing used was editing, coding and tabulation. The results of the study are. Free WIFI significantly effect to Consumer Purchase Decision on Angkringan in district of Karas Magetan Regency.